Hyperacusis and stapes surgery: An observation in fifty patients after stapedotomy - Santos, Mariline (2021)
Objective: To assess hyperacusis after stapedotomy and its possible influencing factors. Study design: Prospective, interventional, and longitudinal study. Setting: A tertiary referral center. Patients: Fifty consecutive patients (35 females, mean age = 46.8 years). Intervention: All patients underwent stapedotomy. The validated Portuguese version of the "Hyperacusis Questionnaire" (HQ) was administered before and two weeks and one month after surgery. Results: No hyperacusis was reported by any patient before surgery. At two weeks after surgery, all patients experienced hyperacusis, with a mean HQ at 16.88 ± 6.54 (range 4-25). One month after surgery, hyperacusis had already resolved in most patients. Gender, preoperative presentation or surgeon had no influence on HQ scores (p > 0.05). Patients with previous contralateral stapedotomy showed lower HQ scores (p = 0.001). Audiological parameters improvement measured at one month after surgery (PTA, SRT and contralateral SRT) were associated with HQ higher scores. Conclusion: This study confirms that hyperacusis is a common complaint after stapedotomy that usually resolves in one month after surgery. The HQ highest scores were registered among patients with the highest audiological gain after surgery. This suggests that hyperacusis may be a positive prognostic factor for audiological success after stapedotomy.